The effect of thyroid function on clinical outcome in patients with heart failure. (14th December 2013) - Chen, Shmuel; Shauer, Ayelet; Zwas, Donna R.; Lotan, Chaim; Keren, Andre; Gotsman, Israel
Abstract : Aims: Thyroid dysfunction is known to effect cardiac function and is a risk factor for developing heart failure (HF). Data regarding the clinical significance of thyroid‐stimulating hormone (TSH) levels alone as a predictor of outcome in patients with HF is sparse. We evaluated the significance of TSH on clinical outcome in a large cohort of patients with chronic HF. Methods and results: Patients with a diagnosis of HF at a Health Maintenance Organization ( n = 5599) were followed for cardiac‐related hospitalizations and death. Median TSH levels were 2.2 mIU/L (interquartile range 1.4–3.5). We divided patients into quartiles based on TSH levels. Median follow‐up time was 434 days and the overall mortality rate was 13.2%. Both a high and a low TSH level was associated with an increased mortality rate. Cox regression analysis after adjustment for other significant predictors demonstrated that the highest TSH quartile was associated with increased mortality compared with those with the lowest mortality [second quartile: TSH 1.4–2.2 mIU/L, hazard ratio (HR) 1.36, 95% confidence interval (CI) 1.08–1.71, P = 0.01]. TSH was also an independent predictor of death and cardiac‐related hospitalization. Analysis of patients not on levothyroxine treatment (78%) demonstrated that TSH was an even stronger predictor of mortality (HR 1.54, 95% CI 1.17–2.03, P = 0.002). Additional analysis based on accepted clinical cut‐offs of TSH demonstrated that increasing TSH levels above normal were independently associated with increased mortality and cardiac‐related hospitalizations. Conclusions: Increased TSH levels are associated with worse clinical outcome in patients with HF. Thyroid imbalance confers significant risk in HF and warrants attention.